The relationship between writing performance and critical thinking dispositions among Malaysian Pre-University students / Nadiah Thanthawi Jauhari - Nadiah , Thanthawi Jauhari (2015)
Studies on writing style tend to characterise Asian learners as group-oriented, harmonyseeking, hierarchical and non-critical thinking, usually differentiated with their Western counterparts who possess critical thinking, horizontal, adversarial and individualistic patterns of behaviour (Atkinson, 1997; Foz, 1994; Ramanathan & Kaplan, 1996). Linguist like Brown (2004), most linguists agree with in an ESL/EFL academic English program, the objective of the curriculum should not be limited to only the linguistic component alone but should also include developing the art of critical thinking. In view of that, the aim of this study is to understand and explore the relationship between English language proficiency in writing and critical thinking dispositions. The California Critical Thinking Disposition Inventory (CCTDI) was used to determine the critical thinking disposition score. The English language proficiency in writing was measured through the research essay assignment which was graded through the holistic grading scheme for writing from a preparatory college. This study involved 138 students. The study aims to achieve three objectives. The first objective was to investigate the critical thinking dispositions profile of students with high, average and low English in their writing. The results showed that for each essay score category (high, average and low), most of the students have ambivalent CCTDI score. The second objective of the study is to examine the extent to which writing correlates with the seven scales of the critical thinking disposition: analyticity, truth-seeking, systematicity, maturity, inquisitiveness, open-mindedness and CT self confidence. It was found that, there were two disposition scales that correlates with the students writing score. These scales are: inquisitiveness and maturity. The third objective is to look at the transition words that students use in their writing when managing the content of their writing. The study found that students with ambivalent score in CCTDI used more transition phrases compared to students with low CCTDI score. Implications in ESL studies were discussed.